고비강도와 고연신을 가지는 다중변형기구 하이엔트로피 합금 개발 - 윤국노; Kook Noh Yoon; 오현석; Hyun Seok Oh; 이제인; Je In Lee; 박은수; Eun Soo Park (대한금속·재료학회지, 59(12), 2021)
In this study we developed a novel (TRIP+TWIP) high entropy alloy (HEA) with high specific strength and large ductility. First, by controlling the atomic constitution of the 3d transition metals (Cr, Mn, Fe, Co, and Ni), we designed a light-weight TRIP-assisted dual-phase HEA with a non-equiatomic composition of Cr 22 Mn 6 Fe 40 Co 26 Ni 6 , which exhibited 5% lighter density than the Cantor HEA. Secondly, we systematically added Al (a lightweight element (2.7 g/㎤), which has a large atomic size misfit with 3d transition metals, and Ferrite stabilizer) up to 5 at.% in Cr 22 Mn 6 Fe 40 Co 26 Ni 6 HEA. With increasing Al content, the phase constitution of the alloy changed from a dual-phase of FCC and HCP (0 to 2.0 at.%) to a FCC single-phase (2.5 to 3.5 at.%), to a dual-phase of FCC and BCC (4.0 to 5.0 at.%). In particular, the (Cr 22 Mn 6 Fe 40 Co 26 Ni 6 ) 97.5 Al 2.5 HEA with the FCC single-phase exhibited a large Hall-Petch coefficient and relatively lower thermal conductivity due to its three times larger atomic size mismatch (δ) than the Cantor HEA, which causes the superior solid solution strengthening effect. Furthermore, the (Cr 22 Mn 6 Fe 40 Co 26 Ni 6 ) 96 Al 4.0 HEA, a boundary composition of BCC precipitation in the FCC phase, exhibited a 10% higher specific strength than the Cantor HEA as well as 50% larger strain, due to the unique TRIP and TWIP complex deformation mechanism. This result shows that the addition of Al in Cr 22 Mn 6 Fe 40 Co 26 Ni 6 HEA can result not only in greater chemical complexity due to the multicomponent high entropy compositions, but also microstructural complexity due to the increase in competing crystalline phases. The confusion effect caused by both complexities lets the alloy overcome the trade-off relationship among conflicting intrinsic properties, such as strength versus ductility (or density). Consequently, these results pave the way for a new design strategy of a novel (TRIP+TWIP) HEA with high specific strength and large ductility. (Received August 19 2021; Accepted September 8, 2021)